Play : how it shapes the brain, opens the imagination, and invigorates the soul - Brown, Stuart L.; Vaughan, Christopher C., 1961- (New York : Avery, 2010)
Discusses the importance of play in terms of health, success, and happiness in adulthood, covering its role in the development of social skills, intelligence, and creativity and its implications for education, business innovation, the future of society, and more.
The promise of play -- What is play, and why do we do it? -- We are built for play -- Parenthood is child's play -- The opposite of play is not work -- Playing together -- Does play have a dark side? -- A world at play.
Includes index.
Includes bibliographical references and index.
Keywords: Play and playthings -- Psychology -- Personal narratives; Play -- Psychological aspects; Play -- Social aspects; Mind and body